GROUP VELOCITY AND DISPERSION COEFFICIENT IN THE DISTRIBUTED SENSOR OF VIBRATION IN FIBRE OPTIC MICHELSON’S INTERFEROMETER CONFIGURATION - Kizlik, Bogdan; Nichoga, Vitalij; Dub, Petro (International Journal of Computing, 2014)
The problem of determination of group velocity and dispersion coefficient in the distributed sensor of vibration in fibre optic Michelson’s interferometer configuration is considered in the report. Influence of acoustic wave on optical wave in a Bragg modulator is described. It is shown that such interferometer can be used as a distributed highly sensitive sensor of mechanical values (vibration, acoustic wave, pressure, displacement).